RRx-001 Exerts Neuroprotection Against LPS-Induced Microglia Activation and Neuroinflammation Through Disturbing the TLR4 Pathway - Fang, Jie; She, Jing; Lin, Fang; Wu, Jun-Chao; Han, Rong; Sheng, Rui; Wang, Guanghui; Qin, Zheng-Hong (Frontiers in Pharmacology, 2022)
Neuroinflammation plays an important role in the pathogenesis of many central nervous system diseases. Here, we investigated the effect of an anti-cancer compound RRx-001 on the neuroinflammation and its possible new applications. BV2 cells and primary microglia cells were used to evaluate the role of RRx-001 in LPS-induced microglial activation and inflammatory response in vitro. And, we found that the increase in the synthesis and release of cytokines and the up-regulation of proinflammatory factors in LPS-treated microglial cells were significantly reduced by RRx-001 pretreatment. As the most classical inflammatory pathways, NF-κB and MAPK signaling pathways were activated by LPS, but were inhibited by RRx-001. Transcription of NLRP3 was also reduced by RRx-001. In addition, LPS induced oxidative stress by increasing the expression of Nox mediated by transcription factors NF-κB and AP-1, while RRx-001 pretreatment ameliorated Nox-mediated oxidative stress. LPS-induced the activation of TAK1, an upstream regulator of NF-κB and MAPK pathways, was significantly inhibited by RRx-001 pretreatment, whereas recruitment of MyD88 to TLR4 was not affected by RRx-001. LPS-primed BV2 condition medium induced injury of primary neurons, and this effect was inhibited by RRx-001. Furthermore, we established a neuroinflammatory mouse model by stereotactic injection of LPS into the substantia nigra pars compacta (SNpc), and RRx-001 dose-dependently reduced LPS-induced microglial activation and loss of TH+ neurons in the midbrain. In conclusion, the current study found that RRx-001 suppressed microglia activation and neuroinflammation through targeting TAK1, and may be a candidate for the treatment of neuroinflammation related brain diseases.